Growing surrounded by decline: do the growing sectors benefit from sharing a labour pool with declining sectors - Gintare Morkute (European Regional Science Association (ERSA), 2014)
Background and motivation: The paper investigates what effects the colocation of growing and declining sectors has on the hiring behaviour of growing sectors in terms of labour pooling and employment growth. Given the importance of geographical proximity in labour matches, the agglomeration literature has suggested that creating dense clusters of (related) economic activities decreases the distances between the firms and the employees, which enables better labour matches and idiosyncratic labour demand absorptions. However, in such clusters the positive effects of labour pooling can be dominated by negative effects of labour poaching, depending on the labour demand of the participants of agglomeration. I build upon the agglomeration literature, but extend it to a framework where the employees flows among sectors in the region are influenced by different growth rates of sectoral labour demand. Data and methods: rich datasets are used with micro-level data linking jobs, firms and employees in the Netherlands 2006-2011. OLS regressions at municipality and NUTS3 area level are conducted. Results and conclusions: The effects of colocation with declining sectors for growing sectors are only marginal. In terms of labour pooling, the easy access to redundant labour force does not encourage the growing sectors to hire more locally. Generally, the employees from declining sectors do not dominate the inflows of declining sectors: the growing sectors focus more on new entrants in the labour market or pooling with stable and other growing sectors; they also tend to hire more outside the region. Moreover, the reluctance to hire locally is understandable: the labour pooling, quite unexpectedly, generally has negative effects on growin sectors' employment growth and even more so in regions with much decline. The overall effects of decline in the region on the employment growth of growing sectors are only statistically significant (and positive) at NUTS3 area level for related decline, probably due to capital flows from declining sectors (it does not correspond to labour force flows). While the implications of the results are quite neutral in terms of location of sectors they are quite negative for redundant employees and regional development in general. The lack of flows from declining to growing sectors indicate that many employees are not able to catch up with the rapid creative destruction. The skills in the redundant sectors are often of little relevance to other sectors.
Keywords: J21; J23; J24; J62; 330